MOSFET technologies for double-Pole four-throw radio-frequency switch - Srivastava, Viranjay M.; Singh, Ghanshyam (Analog Circuits and Signal Processing, 2014)
This book provides analysis and discusses the design of various MOSFET technologies which are used for the design of Double-Pole Four-Throw (DP4T) RF switches for next generation communication systems. The authors discuss the design of the (DP4T) RF switch by using the Double-Gate (DG) MOSFET, as well as the Cylindrical Surrounding double-gate (CSDG) MOSFET.  The effect of HFO2 (high dielectric material) in the design of DG MOSFET and CSDG MOSFET  is also explored. Coverage includes comparison of Single-gate MOSFET and Double-gate MOSFET switching parameters, as well as testing of MOSFETs parameters using image acquisition.  ·         Provides a single-source reference to the latest technologies for the design of Double-gate MOSFET, Cylindrical Surrounding double-gate MOSFET and HFO2 based MOSFET; ·         Explains the design of RF switches using the technologies presented and simulates switches; ·         Verifies parameters and discusses feasibility of devices and switches.